Tác động nhân quả của trợ cấp nhiên liệu trong ngành khai thác cá ngừ đại dương Việt Nam - Nguyễn Ngọc , Duy (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study examines the impact of fuel subsidies on the technical and economic efficiency of Vietnam’s oceanic tuna longline fleet. The research utilizes data from 122 vessels during the 2024 fishing season and employs a double-robust estimation approach to identify the causal effects of two intervention factors, including net fuel price and subsidy intensity. The findings reveal that higher net fuel prices are associated with greater fuel efficiency and profitability. However, these benefits diminish when the net fuel price becomes excessively high. Conversely, higher subsidy intensity is linked to lower fuel efficiency and profitability, suggesting that broad-based support policies weaken conservation incentives and undermine economic performance. The evidence underscores the need for policy reform toward targeted subsidies tied to operational efficiency, consistent with the WTO Fisheries Subsidies Agreement and the objective of promoting sustainable offshore fisheries development.